Findings and implications of the relationship of pre-service educators, their university tutor and in-service teachers regarding professional development in science in the primary school system. Issue 5 (20th October 2018) - Overton, David
ABSTRACT: This paper explores the professional needs of pre-service teachers, their university tutor and in-service teachers in terms of their subject and pedagogical content knowledge. It does so through an examination of these professionals' participation in the learning experiences of children. The context for this participation is the children's engagement with activity in a local children's university in the UK. The study adopts a grounded theory methodology incorporating analysis of the open coding of unstructured interview transcripts. The study provides insight into practitioners' preferred modes of learning with consideration of the effectiveness of formal and non-formal contexts. There is evidence that adoption of a non-formal approach to teacher education can be beneficial if pre-service teachers can learn in the presence of practising teachers and the university tutor. The teachers learn from the practice modelled by the university tutor. The tutor benefits from developing their practice and effecting moderation of the school–university partnership.